Phylogenetic Inferences and Historical Biogeography of Onocleaceae - Jing Zhao; Jia-Guan Wang; Yu-Ping Hu; Chuan-Jie Huang; Shao-Li Fang; Zi-Yue Wan; Rong-Juan Li; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Plants)
The family Onocleaceae represents a small family of terrestrial ferns, with four genera and around five species. It has a circumboreal to north temperate distribution, and exhibits a disjunct distribution between Eurasia and North America, including Mexico. Historically, the taxonomy and classification of this family has been subject to debate and contention among scholars, leading to contradictory classifications and disagreements on the number of genera and species within the family. Furthermore, due to this disjunct intercontinental distribution and the lack of detailed study across its wide range, this family merits further study to clarify its distributional pattern. Maximum likelihood and Bayesian phylogenetic reconstructions were based on a concatenated sequence dataset for 17 plastid loci and one nuclear locus, which were generated from 106 ingroup and six outgroup taxa from three families. Phylogenetic analyses support that Onocleaceae is composed of four main clades, and Pentarhizidium was recovered as the first branching lineages in Onocleaceae. Molecular dating and ancestral area reconstruction analyses suggest that the stem group of Onocleaceae originated in Late Cretaceous, with subsequent diversification and establishment of the genera Matteuccia, Onoclea, Onocleopsis, and Pentarhizidium during the Paleogene and Neogene. The ancestors of Matteuccia, Onoclea, and Onocleopsis could have migrated to North America via the Beringian land bridge or North Atlantic land bridge which suggests that the diversification of Matteuccia + Onoclea + Onocleopsis closely aligns with the Paleocene-Eocene Thermal Maximum (PETM). In addition, these results suggest that Onocleaceae species diversity peaks during the late Neogene to Quaternary. Studies such as this enhance our understanding of the mechanisms and climatic conditions shaping disjunct distribution in ferns and lycophytes of eastern Asia, North America, and Mexico and contribute to a growing body of evidence from other taxa, to advance our understanding of the origins and migration of plants across continents.